Assessment of Explicitly Stated Interval Change on Noncontrast Head CT Radiology Reports - Braileanu, M.; Crawford, K.; Key, S.R.; Mullins, M.E. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Consistent and standardized reporting of interval change for certain diagnoses may improve the clinical utility of radiology reports. The purpose of this study was to assess explicitly stated interval change of various findings in noncontrast head CT reports.MATERIALS AND METHODS: A retrospective review was performed on successive noncontrast head CT radiology reports from the first 2 weeks of January 2014. Reports with at least 1 prior comparison CT scan were included. Reports with normal examination findings and those that made comparison with only other types of examinations (eg, MR imaging) were excluded. Descriptive and subgroup statistical analyses were performed.RESULTS: In total, 200 patients with 230 reports and 979 radiographic findings were identified. The average interval between reports was 344.9 ± 695.9 days (range, 0–3556 days). Interval change was mentioned 67.3% (n = 659) of the time for all findings (n = 979). Explicitly stated interval change was significantly associated with nonremote findings (P < .001) and generalized statements of interval change (P < .001). The proportion of interval change reported ranged from 95.3% of the time for hemorrhagic to 36.4% for soft-tissue/osseous categorizations.CONCLUSIONS: Interval change reporting was variable, mentioned for 67.3% of noncontrast head CT report findings with a prior comparison CT scan. Structured radiology reports may improve the consistent and clear reporting of interval change for certain findings.ICinterval change